PENGARUH MEDIA WORDWALL TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS IV SDN PANARAGAN 1 - Sumiarsih; Nurlinda Safitri; Yuyun Yuniar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the influence of wordwall media. This research uses a quasi-experimental method. The research was carried out at the Panaragan I state elementary school in Bogor city, class IV-A and IV-B, odd semester 2024/2025. The data processing technique used is the data analysis prerequisite test which includes a normality test and homogeneity test, then a hypothesis test is carried out using the t test. based on data analysis, the results of learning Pancasila education subjects through wordwall media obtained an average N-Gain of 69 with a complete learning result of 100%, while not using wordwall media obtained an average N-Gain value of 44 with a complete learning result of 86% . The results of hypothesis testing state that H0 is rejected and Ha is accepted because tcount (4.80769) > ttable (2.004879). Based on the research results above, it can be concluded that there is an influence of wordwall media on learning outcomes in the Pancasila education subject in class IV at SDN Panaragan I.